Distance Learning Students' Perspectives of Academic Procrastination: A Qualitative Investigation - Fang, Ruoyu; White, Robert (The Journal of continuing higher education, 2025)
This study explores academic procrastination among postgraduate distance learners, a topic that has received limited attention. Through qualitative interviews with participants, the authors conducted thematic analysis on their experiences. Three overarching themes emerged: perception, reasons, and reflection of academic procrastination among distance learners. Notably, participants frequently procrastinated, primarily due to study-life balance challenges. Surprisingly, participants expressed overall satisfaction with their academic performance despite procrastination tendencies. They considered procrastination a conscious choice, prioritizing other life commitments over studying. This study sheds light on the influence of external factors on procrastination behavior in distance learning. The findings suggest that academic procrastination is prevalent among distance learning students, with study-life balance being a significant predictor. Participants' satisfaction with their academic performance suggests that procrastination may be a deliberate choice. This research highlights the need for tailored interventions to address procrastination in distance education settings.